HPB P12 Pancreatoduodenectomy for confirmed malignancy: A complication profile from the Recurrence After Whipple's (RAW) study. (7th December 2022) - Russell, Thomas; Labib, Peter; Aroori, Somaiah
Abstract: Background: Pancreatoduodenectomy (PD) is recommended in fit patients with resectable cancer affecting the pancreatic head or periampullary region. This operation can provide a cure in some patients but it remains high-risk. Although perioperative mortality rates have fallen below 2.0% in high-volume centres, complications still affect up to 50% of cases. Due to the nature of the resection and the subsequent anastomoses required, a number of general and procedure-specific complications may occur. Whilst a number of smaller studies have reported on procedure-specific outcomes, no large recent studies have aimed to put together a comprehensive complication profile. This international multicentre retrospective study aimed to calculate the incidence and severity of all PD complications in a cohort of patients with confirmed pancreatic ductal adenocarcinoma (PDAC), ampullary adenocarcinoma (AA) or cholangiocarcinoma (CC). Methods: Patients were included if they underwent PD for histologically-confirmed PDAC, AA or CC at one of 28 participating units between 01/06/2012 and 31/05/2015. This end date was selected so that five-year follow-up data was available for all patients. Data was collected on the following complications: clinically relevant postoperative pancreatic fistula (CR-POPF), bile leak, gastrojejunal leak, postpancreatectomy haemorrhage (PPH), delayed gastric emptying (DGE), acute kidney injury (AKI), cardiac arrythmia, chest infection, cholangitis, chyle leak, Clostridium difficile infection, ileus, intra-abdominal collection, liver abscess, myocardial infarction (MI), pancreatic necrosis, pancreatitis, portal vein (PV)/superior mesenteric vein (SMV) thrombosis, sepsis of unknown origin, splenic vein thrombosis, surgical site infection (SSI), urinary tract infection (UTI), deep vein thrombosis (DVT), and pulmonary embolism (PE). Other complications could be entered by the data collector in free text. CR-POPF, bile leak, gastrojejunal leak, PPH and DGE were defined and categorised using internationally agreed definitions. All other complications were diagnosed based on predefined clinical and/or radiological criteria. All complications were graded using the Clavien-Dindo (CD) classification. When comparing patients who developed at least one complication to those who developed no complications, medians were compared using the Mann-Whitney U test. Other comparisons were made using Fisher's exact test. Results: The analysis included 1, 465 patients. Median age was 67 years and 44.2% were female. In total, 49.1% of patients experienced at least one complication; 25.4% of these were CD grade I, 48.5% were grade II, 17.1% were grade III, 5.7% were grade IV and 3.2% were grade V. CR-POPF affected 7.1% of cases (grade B: 81, grade C: 23), bile leak affected 2.7% (grade A: 13, grade B: 17, grade C: 10) and gastrojejunal leak affected 1.7% (grade A: 5, grade B: 8, grade C: 7). PPH was reported in 5.6% of cases (grade A: 17, grade B: 39, grade C: 26) and 11.3% developed DGE (grade A: 73, grade B, 58, grade C: 35). Seventy-seven patients (5.2%) had an unplanned return to theatre and 90-day mortality was 3.6%. The most common cause of death was PPH, followed by POPF, intra-abdominal sepsis and renal failure. Patients who experienced morbidity were significantly more likely to be female (41.3% vs 46.9%, p=0.03) or have a preoperative cardiovascular (49.3% vs 33.7%, p<0.0001) or respiratory co-morbidity (13.6% vs 8.3%, p=0.001). They were also less commonly ASA grade I or II (62.9% vs 70.0%, p=0.005). Conclusions: In our international multicentre study of patients who underwent PD for confirmed malignancy, overall morbidity was 49.1% and perioperative mortality was 3.6%. Whilst minor complications were common, severe complications were rare. The incidences of CR-POPF, bile leak, gastrojejunal leak, and PPH were 7.1%, 2.7%, 1.4% and 5.6%, respectively. The most common cause of death was PPH. It is important that surgeons who perform PD have a sound understanding of its complication profile. This will allow them to evaluate their own performance when auditing and guide the consenting process.